Inpatient satisfaction with hospital services in Indonesia: A systematic review - Hapsari, Kanya; Sriatmi, Ayun; Kartini, Apoina (International Journal Labs, 2023)
Inpatient satisfaction is influenced by the quality of services provided by the hospital. The quality of service in question consists of Reliability, Assurance, tangibility, Empathy and Responsiveness. The aim of this research is to estimate and analyze the influence of the quality of inpatient services on patient satisfaction in hospitals. This research is a systematic review and metaanalysis research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= InPatient; I = Good service quality; C= Poor Service Quality; O= Patient Satisfaction. Electronic literature was searched in 4 databases : Google Scholar, Research Gate, PubMed and Elsevier, for articles published on 2020-2023. With keywords including